BURDEN AMONG THE CARE GIVERS OF TRAUMATIC BRAIN INJURED PATIENTS ADMITTED IN CRITICAL CARE UNITS - Kusuma; Nagarajaiah (Indian Journal of Psychiatric Nursing, 2016)
Traumatic brain injury is a catastrophic and life altering experience which creates major problems to the victims, family and society. This study was conducted to assess the level of burden on care givers of critically ill traumatic brain injury patients hospitalized in critical care units at NIMHANS. Descriptive research design was used for the study. A total of 100 subjects were selected using simple random sampling method. Socio-demographic data schedule and Zarit burden interview was used to collect the information for a period of 3 months. Results showed that the burden mean score and standard deviation was70.26± 5.764. Socio demographic variables showed no influence on burden in the study subjects. The study concluded overall findings of this study showed increased burden scores in care givers of traumatic brain injury patient which suggest that nurses need to conduct motivation and interventional programmes to improve the care giver's coping and reduce their burden level.